The politics of music in international organizations in the first half of the twentieth century - Sibille, Christiane (New global studies, 2017)
This article examines the activities of international organizations in the field of music in the first half of the twentieth century. Despite the common association with music as a universal language and international art, it has not often been systematically investigated in the context of institutionalized international co-operation. By focusing on the International Musical Society, the International Society for Musicology, the International Society for Contemporary Music, the Permanent Council for the International Co-operation between Composers, and the activities of the League of Nations in the field of music, it analyzes common topics and different strategies to establish stable networks and co-ordinate the flow of information. By locating the activities of the experts involved along the two analytical axes of nationalization/internationalization and politization/standardization, it becomes not only possible to integrate the activities in the field of music into the history of international organizations, but also to gain important insights into the international and political origin of musicology as an academic discipline.